Blood coagulation system in patients with chronic kidney disease: a prospective observational study. Issue 5 (1st June 2017) - Huang, Meng-Jie; Wei, Ri-bao; Wang, Yang; Su, Ting-yu; Di, Ping; Li, Qing-ping; Yang, Xi; Li, Ping; Chen, Xiang-mei
Abstract : Objectives: Thromboembolic events are the major factor affecting the prognosis of patients with chronic kidney disease (CKD). Haemostatic alterations are possible causes of these complications, but their roles remain poorly characterised. In the prospective observational study, we investigated the entire coagulation process in patients with CKD to elucidate the mechanisms of their high thromboembolic risk. Methods: A total of 95 patients with CKD and 20 healthy controls who met the inclusion criteria were consecutively recruited from September 2015 to March 2016. The platelet count, platelet aggregation, von Willebrand factor antigen (vWF:Ag), vWF ristocetin cofactor activity (vWF:RCo), fibrinogen, factor V (FV), FVII, FVIII, antithrombin III, protein C, protein S, D-dimer, standard coagulation tests and thromboelastography were measured in patients with CKD and controls. Associations between the estimated glomerular filtration rate (eGFR) and haemostatic biomarkers were tested using multivariable linear regression. Results: The adjusted and unadjusted levels of vWF:Ag, vWF:RCo, fibrinogen, FVII, FVIII and D-dimer were significantly higher in patients with CKD than that in the healthy controls, and were elevated with CKD progression. However, after adjustment for baseline differences, platelet aggregation and thromboelastography parameters showed no significant differences between patients with CKD and healthy controls. In the correlation analysis, vWF:Ag, vWF:RCo and FVIII were inversely associated with eGFR (r=−0.359, p<0.001; r=−0.391, p<0.001; r=−0.327, p<0.001, respectively). During the 1-year of follow-up, one cardiovascular event occurred in patients with CKD 5 stage, whereas no thromboembolic event occurred in the CKD 3 and 4 and control groups. Conclusions: Patients with CKD are characterised by endothelial dysfunction and increased coagulation, especially FVIII activity. The abnormal haemostatic profiles may contribute to the elevated risk of thrombotic events but further longer-term study with large samples is still required to more precisely determine the relationship between the elevation of procoagulant factors and clinical outcomes.